2014
DOI: 10.12669/pjms.304.4546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant human growth hormone therapy on carbohydrate, lipid, and protein metabolisms of children with Turner syndrome

Abstract: Objective: To study the effect of recombinant human growth hormone (rhGH) therapy on carbohydrate, lipid and protein metabolisms of Turner syndrome (TS). Metho d s: Total 45 patients with TS admitted between Jul. 2008 and Jun. 2011 were involved in this study. All patients received the clinical evaluation of body fat, plasma lipids, proteins and oral glucose tolerance test (OGTT) before and after rhGH therapy. Results : Our results indicated a significant decrease of body fat (FAT%) from 23.56±4.21 to 18.71±2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…In healthy adolescents, cortical bone BMD was found to increase with age, with higher annual accrual rates in girls compared to boys19. The current study demonstrated a different pattern in girls with TS, with no significant increase in BMD with increasing age and HRT did not appear to alter the rate of change in BMD with age.…”
Section: Discussioncontrasting
confidence: 56%
“…In healthy adolescents, cortical bone BMD was found to increase with age, with higher annual accrual rates in girls compared to boys19. The current study demonstrated a different pattern in girls with TS, with no significant increase in BMD with increasing age and HRT did not appear to alter the rate of change in BMD with age.…”
Section: Discussioncontrasting
confidence: 56%
“…An earlier study investigated GH's effects on glucose, lipid, and protein metabolism in TS patients. No significant change in HOMA-IR during treatment was detected (26) . This could be explained by the short duration of GH therapy.…”
Section: Disscusionmentioning
confidence: 83%
“…Other body composition indicators, such as fat and water percentages, did not show statistically significant variances between the two subgroups. A longer period of follow-up is necessary to demonstrate the impact of growth hormone treatment on several body composition markers (10,25,26) .…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GH reduces blood pressure, LDL and total cholesterol, without negative effects on insulin resistance. 14,15 Gonadal dysgenesis potential cause of dyslipidemia in TS. Hormone replacement and vascular functions.…”
mentioning
confidence: 99%